Collaboration, Incentives, and Organizational Culture: Drivers of Knowledge Sharing in Automotive Companies - Nurul Kholifah; Gilang Ramadhan (DPPM Universitas Pelita Bangsa, 2025)
Knowledge sharing behavior in companies is used to measure the extent to which individuals or employees are willing and active in exchanging information, experiences, and ideas with colleagues. Factors that influence knowledge sharing behavior are collaborative work environment and incentives to share knowledge. This study aims to examine the direct and indirect relationships between the variables of collaborative work environment, incentives to share knowledge, organizational culture and knowledge sharing behavior with the object of research, namely automotive companies in the MM2100 area. The research was conducted using quantitative methods. The population used is all employees who work in the MM2100 area with a sample size of 133 respondents, the sampling technique used is the probability sampling technique with the purposive sampling method. Data collection is done through google form in filling out an online survey. Data analysis in this study used the help of the SmartPLS software program version 3.0. The novelty of this study lies in integrating organizational culture as a mediating factor that has not been widely tested in Indonesian manufacturing, thereby offering a fresh perspective on how structural and motivational elements jointly shape knowledge sharing. Theoretically, the findings contribute to expanding social exchange and organizational learning theories by clarifying the mechanisms through which collaboration and incentives foster knowledge sharing behavior. Practically, the study provides important implications for HR managers in the automotive sector to design incentive systems, strengthen collaborative practices, and cultivate cultures that encourage continuous knowledge exchange to improve innovation and competitiveness.